2021
DOI: 10.1093/molbev/msab110
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Basis of Striking Fin Shapes and Colors in the Fighting Fish

Abstract: Resolving the genomic basis underlying phenotypic variations is a question of great importance in evolutionary biology. However, understanding how genotypes determine the phenotypes is still challenging. Centuries of artificial selective breeding for beauty and aggression resulted in a plethora of colors, long fin varieties, and hyper-aggressive behavior in the air-breathing Siamese fighting fish (Betta splendens), supplying an excellent system for studying the genomic basis of phenotypic variations. Combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(96 citation statements)
references
References 75 publications
1
89
2
Order By: Relevance
“…S2A). The whole pedigree of this population from parental (P) to F 2 generations were raised under normal laboratory conditions and had been previously used for mapping fin and pigmentation related traits [ 23 ]. The F 1 population showed a sex ratio of F: M ≈ 1:5 while the overall sex ratio across these two F 2 families was F: M ≈ 1:2.8 (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2A). The whole pedigree of this population from parental (P) to F 2 generations were raised under normal laboratory conditions and had been previously used for mapping fin and pigmentation related traits [ 23 ]. The F 1 population showed a sex ratio of F: M ≈ 1:5 while the overall sex ratio across these two F 2 families was F: M ≈ 1:2.8 (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [10] investigated the same phenotype using F ST scan and located a 1.3Mb region on chromosome 16 (chromosome 9 in their assembly) that contains our GWAS peak. They suggested, based on gene expression analyses, that the causal gene could be kcnh8 [10]. However, this gene resides outside of the associated locus on chromosome 16 identified in this study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B. splendens is easy to breed and maintain, and provides a useful resource for exploration of the genetic basis of behavior and morphology in vertebrates, due to the high degree of intraspecific variability and the vast number of characterized phenotypes. Although researchers have examined the inheritance of body color, fin length and sex in classic crosses in the 1930s to 1940s [3][4][5][6][7][8][9], relatively little was known until a recent study investigated the double tail, elephant ear, albino and fin spot phenotypes [10]. Here we report a high-quality chromosomal-level genome assembly of a female B. splendens, resequencing data of 727 domesticated individuals, and resequencing data of 59 individuals from six other species in the B. splendens complex.…”
Section: Introductionmentioning
confidence: 99%
“…6,28 In over 20 aquaculture species, CRISPR/Cas9 system has been used in studies on gene functions and breeding (Table 1). These species include Nile tilapia (O. niloticus), 23,79 Atlantic salmon (Salmo salar), 26,80,81 Atlantic killifish (Fundulus heteroclitus), 25 oriental prawn (Exopalaemon carinicauda), 82 Labeo rohita, a farmed carp (known as rohu), 83 common carp (Cyprinus carpio), 76,84 The Burton's mouth-brooder (Astatotilapia burtoni), 61 Chinese tongue sole (Cynoglossus semilaevis), 85 Red sea bream (Pagrus major), [86][87][88] channel catfish (Ictalurus punctatus), [89][90][91] grass carp (Ctenopharyngodon idella), 92 sterlet (Acipenser ruthenus), 93 olive flounder (Paralichthys olivaceus), 27,94,95 Pacific oyster (Crassostrea gigas), 96 blunt snout bream (Megalobrama amblycephala), 97 white prawn (Exopalaemon carinicauda), 82 fighting fish (Betta 98 and other species. 12 Studies on genome editing in aquaculture species confirmed that the CRISPR/Cas system is highly efficient, has lower off-target tendencies, and is able to generate long fragment deletions.…”
Section: S Tatus Of G Enome Ed Iting In Aq Uacu Ltu Rementioning
confidence: 99%